Efects of electron blocking layer thickness on the electrical and optical properties of AlGaN based deep ultraviolet light emitting diode - Hairol Aman, Mohammad Amirul; Ahmad Noorden, Ahmad Fakhrurrazi; Abdul Kadir@Jaafar, Muhammad Zamzuri; Danial, Wan Hazman; Daud, Suzairi (Springer, 2024)
The aluminum gallium nitride (AlGaN)-based deep-ultraviolet light-emitting diode (DUV-LED) has been a prominent device due to its contribution in various fields. The electron blocking layer (EBL) is an additional layer in the epitaxy of the DUV-LED with the aim of reducing the overflow of electrons and improving the hole injection, consequently increasing the performance of the DUV-LED. However, the threshold of the EBL thickness and its influence on the electrical and optical properties is still not fully understood. Hence, the purpose of this research is to investigate the effects of varying the EBL thickness, ranging from 5 nm up to 60 nm, and investigate the threshold of EBL thickness for the AlGaN-based DUV-LED. The analysis includes the internal quantum efficiency (IQE), luminescence spectrum, band diagram behavior, and the current density of the carrier. It is found that EBL thickness of 15 nm produces the highest IQE (39.69%) for the DUV-LED with a single quantum well structure, where the wavelength emitted is ~ 257 nm, which is within the ultraviolet C (UVC) range.